2001
DOI: 10.1016/s0092-8674(01)00316-6
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the 14-3-3ζ:Serotonin N-Acetyltransferase Complex

Abstract: Serotonin N-acetyltransferase (AANAT) controls the daily rhythm in melatonin synthesis. When isolated from tissue, AANAT copurifies with isoforms epsilon and zeta of 14-3-3. We have determined the structure of AANAT bound to 14-3-3zeta, an association that is phosphorylation dependent. AANAT is bound in the central channel of the 14-3-3zeta dimer, and is held in place by extensive interactions both with the amphipathic phosphopeptide binding groove of 14-3-3zeta and with other parts of the central channel. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
365
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(396 citation statements)
references
References 46 publications
22
365
1
2
Order By: Relevance
“…The two additional structures of 14-3-3ζ and 14-3-3τ were determined bound to a phosphopeptide or a sulfate group, respectively. In addition, the structure of 14-3-3ζ has the same overall fold compared to the published structures of the ζ and τ isoforms [15]. The structure of 14-3-3σ has the same overall fold as the known fold of the ζ and τ isoforms (Fig.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…The two additional structures of 14-3-3ζ and 14-3-3τ were determined bound to a phosphopeptide or a sulfate group, respectively. In addition, the structure of 14-3-3ζ has the same overall fold compared to the published structures of the ζ and τ isoforms [15]. The structure of 14-3-3σ has the same overall fold as the known fold of the ζ and τ isoforms (Fig.…”
Section: Resultsmentioning
confidence: 58%
“…Structural comparison of 14-3-3σ σ σ σ σ, τ τ τ τ τ and ζ ζ ζ ζ ζ We compared our structure of 14-3-3σ to the previously published structures of 14-3-3ζ and 14-3-3τ [12,15,22,23]. Only the structure of 14-3-3ζ solved by Liu et al was determined in an unliganded form, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study involving cocrystallization of 14-3-3 with the enzyme serotonin N-acetyltransferase (AANAT) provides a more comprehensive understanding of the 14-3-3-target structure (Obsil et al, 2001). As the only existing example of a structure of 14-3-3 bound to a target protein, this study provides a somewhat different picture than that derived from studies with short peptides; full-length AANAT, which contains two potential 14-3-3 binding sites (e.g., T31 and S205), forms exclusively 1:2 stoichiometric complexes with 14-3-3 in vitro, suggesting that a dimeric 14-3-3 binds to a single AANAT polypeptide at two sites.…”
Section: Discussionmentioning
confidence: 99%
“…This protein family can either positively modulate enzyme activity, in the cases of serotonin Nacetyltransferase (Obsil et al 2001) and Protein Kinase C (Van Der Hoeven et al 2000), or negatively modulate activity, such as with CaM-kinase kinase (Davare et al 2004). Specifically in the ERK pathways, 14-3-3 does not impact the activity of MEK (Shimizu et al 1994), but it has been reported to stimulate the enzyme upstream from MEK, Raf (Freed et al 1994) ) and associates with other upstream kinases in the pathway (Yamamori et al 1995).…”
Section: Discussionmentioning
confidence: 99%